Foreign Ownership, Corporate Governance Mechanism and Technical Efficiency of Indonesia Banking Industry - Abdul Ghofar; Farisan Noviandry (University of Merdeka Malang, 2018)
A large number of commercial banks in Indonesia are considered not ideal for the future of Indonesian banking because most of these banks are considered unhealthy and inefficient. This research aimed to examine the input and output efficiency in the Indonesian banking industry and the influence of foreign ownership and corporate governance mechanisms measured by the size of the board of commissioners and the percentage of the independent commissioner on technical efficiency using a non-parametric approach of Data Envelopment Analysis (DEA). This research used 50 foreign exchange commercial banks of Indonesia from 2012-2014. The results of DEA indicated that the efficiency of foreign exchange commercial banks has increased significantly during the observation period. Other results showed that banks with foreign ownership had a strong and positive link with technical efficiency. In line with the established literature on emerging markets, foreign ownership banks appear to be more efficient than banks with fully domestic ownership. However, the board of commissioner size showed no effect on banks technical efficiency. The percentage of independent commissioner showed a negative effect on efficiency that consistent with the argument that tighter monitoring of board of commissioners might impede performance.JEL Classification: D61, G35, M41DOI: https://doi.org/10.26905/jkdp.v22i4.2461